Clinical outcomes of open hip abductor tendon repair with minimum two-year follow-up. Issue 4 (July 2022) - Balazs, George C; Dooley, Matt; Wang, Dean; O'Sullivan, Eilish; Kelly, Bryan T
Background: The results of open hip abductor tendon repair remains poorly defined. We sought to present the results and complications of this procedure using modern suture anchor fixation. Materials and Methods: Our prospective institutional hip preservation registry was queried for all patients who underwent open hip abductor tendon repair with minimum 2-year follow-up were identified. Demographic, clinical, intraoperative, and functional outcome details were recorded. Patient-reported outcome scores (PROs) including the modified Harris Hip Score (mHHS), HOS-ADL, HOS-S, and iHOT-33 were collected for the preoperative and final postoperative state. Risk factors for lower final mHHS and change in mHHS were analysed using a multiple regression model. Results: A total of 21 patients with mean 48 months clinical follow-up (range 24–84 months). Median mHHS improved from 49.50 preoperatively to 82.50 postoperatively ( p  < 0.001), median HOS-ADL improved from 60.29 to 82.35 ( p  = 0.001), median HOS-S improved from 37.50 to 60.00 ( p  = 0.04), and median iHOT-33 improved from 29.81 to 70.15 ( p  = 0.001). All patients had +4 or +5 hip abductor strength at final in-person examination at mean 17 months postoperatively. All patients with a preoperative Trendelenburg gait had complete resolution at final examination. There 2 complications, and no patient had re-tear or revision surgery. LCEA < 25° and a history of prior ipsilateral hip surgery were independently predictive of smaller improvement in mHHS at final follow-up. Conclusions: Open abductor tendon repair is a safe and effective procedure that provides sustained symptomatic and functional improvements at mid-term follow-up.